DUKUNGAN SUAMI DENGAN KESIAPAN IBU DALAM PEMBERIAN ASI PADA BAYI DI PUSKESMAS BULU KABUPATEN SUKOHARJO - Fakhidah, Luluk Nur; Rosita, Siskana Dewi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
For decreasing morbidity in children, World Health Organization (WHO) and United Nations Children’s Fund (UNICEF) recommend giving exclusive breastfeeding for infants aged 6-12 months. In Indonesia, exclusive breast feeding coverage nationally in 2015 was 55.7% that was far from the achievement target in exclusive breastfeeding globally that It should be 80%. Whereas in 2016 it was known that the total infants who were given exclusive breastfeeding for 0-6 month infants were 29,5% and for 0-5 month infants were 54% (Kemenkes RI,2017). The purpose of this research was knowing the relationship of husband’s support with mother’s readiness breastfeeding infant. The type of this research was observational analytic with cross sectional approach. Samples of this research were all mothers who were in the third trimester at working area at PukesmasBulu, Sukoharjo district with 36- 40 weeks gestational age from November to December 2018. The instruments that were used were univariate and bivariate using chi square test. The result of this research showed the Asympvalue. Sig (2-sided) was 0.175 > 0.05. For the result, it could be concluded that there was no relationship of husband’s support with mother’s readiness breastfeeding infant with the strength of correlation. It could be seen through r value that was worth 0.220. It meant that the strength of relationships among variable was weak. Keywords: Husband’s support, Mother’s Readiness, Giving Exclusive Breastfeeding